Immunization and Immunization Coverage According to National Immunization Schedule for Children Population: Cross-Sectional Multi-Centre Study - L. S. Namazova-Baranova; M. V. Fedoseenko; P. R. Grinchik; A. A. Girina; S. V. Kovalev; A. V. Mazokha; E. D. Makushina; E. I. Malinina; A. Yu. Musikhina; O. A. Perminova; N. Y. Plenskovskaya; T. E. Privalova; et al. (Union of pediatricians of Russia, 2021)
Background. Monitoring of documented vaccination is one of the indicators of the epidemiological supervision quality of preventive vaccination. It is crucial for epidemical situation prevention. Objective. The aim of the study is to estimate immunization and immunization coverage levels according to National Immunization Schedule (NIS) for children population in Russia. Methods. Immunization rates were estimated according to preventive vaccination cards (form №063/y) and children development cards (form №112/y) among children aged from 6 months to 15 years in 8 towns of Russia. Immunization was determined by the ratio of people who has fully performed all the vaccines from NIS (version of the year 2014), while immunization coverage - by the ratio people who has received at least one dose of corresponding vaccine. Results. The study has included data from 2,687 vaccinated children. The highest levels of immunization and immunization coverage were against tuberculosis (98.1% each), hepatitis B (85.9% and 96.5%), measles, mumps and rubella (84.4% and 93.9%). Immunization against diphtheria, pertussis and tetanus significantly differed from their immunization coverage (60.5% and 94.9%), as well as for poliomyelitis (65.0% and 94.9%). Relatively low immunization and immunization coverage levels were observed for pneumococcal infection (27.6% and 47.1%) and influenza (5.8% and 30.5%). The increase in the immunization level with age was observed for all vaccines, except pneumococcal vaccine. Conclusion. Immunization and immunization coverage against infections included in NIS vary significantly. The highest immunization and immunization coverage levels for all age groups were revealed for tuberculosis vaccine, and the lowest - for influenza vaccine.